Histopathological evidence for macrophage activation driving post‐transfusion hyperhaemolysis syndrome. (24th April 2019) - Win, Nay; Lucas, Sebastian; Hebballi, Sangam; McKernan, Angela; Hamilton, Rosie; Robinson, Ivan; Chen, Frederick
Summary: Post‐transfusion hyperhaemolysis syndrome (PTHS) is a rare life‐threatening transfusion complication reported mainly in sickle cell patients. Its pathogenesis is poorly understood. Antibody‐mediated haemolysis and bystander effect have been proposed as putative mechanisms, but in half of cases, red cell antibodies are undetectable, and PTHS develops despite transfusion of cross‐matched compatible RBC. An alternate hypothesis proposes activated macrophages as the main drivers of red cell destruction through direct phagocytosis. We report the histopathological findings of two patients with PTHS showing extensive macrophage expansion and erythrophagocytosis, supportive of macrophage activation driving PTHS. This supports a possible role for novel therapies that target macrophage activation.